Evaluation of Colleague Relations of Accountants in Accounting Service Firms in Hanoi - Nguyen Van Thu; Nguyen Van Tri (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
The main objective of this study was to identify, evaluate, and to measure the attributes of colleague relations of accountants in accounting service firms in Hanoi, Vietnam. The study was based on a field survey using a semi-structured questionnaire on a sample of 150 accountants. But only 125 filled questionnaires were satisfactory and therefore included in the analysis. By using seceral statistical analytical tools, i.e. descriptive statistics, Cronbach’s Alpha analysis, and Independent T-test, the study has identified and measured four (4) attributes of colleague relations of accountants in accounting service firms in Hanoi, Vietnam that have great effects on employees (or in this case study, accountants). There is not, statistically, significant difference in the level of colleague relations of accountants in accounting service firms in Hanoi from these different age and work experiences. Based on the findings, some recommendations are given for accounting service firms to improve the colleague relations of accountants.